Intravesical Oxybutynin for Urgent Bladder Rescue in a Newborn with Posterior Urethral Valves - Ada Molina Caballero; Alberto Pérez Martínez; Concepción Goñi Orayen; Gemma Sierra Colomina; Ana Lavilla Oiz; Yolanda Armendariz Cuevas (Georg Thieme Verlag KG, 2019)
Posterior urethral valves are the most common cause of bladder outlet obstruction in male newborns. Initial catheter drainage alleviates the urethral obstruction before definitive management by valve ablation. Newborns with posterior urethral valves often present with hypercontractile bladders that may inhibit upper tract drainage despite bladder catheterization. Anticholinergic agents are commonly used to treat detrusor hyperactivity, with oxybutynin being the most commonly used. We report the first case of a newborn with posterior urethral valves and ureterovesical junction obstruction caused by detrusor hypertrophy who underwent urgent intravesical instillation of oxybutynin at high doses in an attempt to avoid a diversion procedure.